The Bruise - Zurawski, Magdalena (Book collections on Project MUSE., 2008)
Winner of Ronald Sukenick Prize for Innovative Fiction The Bruise is a prize-winning novel of imperative voice and raw sensation. In the sterile dormitories and on the quiet winter greens of an American university, a young woman named M & mdash; deals with the repercussions of a strange encounter with an angel, one that has left a large bruise on her forehead. Was the event real or imagined? The bruise does not disappear, forcing M & mdash; to confront her own existential fears and her wavering desire to tell the story of her imagination. As a writer, M & mdash; is breathless, desperate, and obsessi.